Young man with sudden severe hip pain secondary to femoral neck stress fracture. (26th October 2016) - Petrin, Ziva; Sinha, Anupam; Gupta, Sunny; Patel, Mitesh K
Abstract : Femoral neck stress fractures have been described in military recruits and athletes. Early recognition and aggressive treatment are important, as femoral neck stress fractures have a high potential for complications and even uncomplicated fractures require an extensive course of rehabilitation. Tension-side (superolateral) stress fractures of the femoral neck are at high risk for complications such as displacement, non-union and avascular necrosis, and need to be treated surgically, while compression-side (inferomedial) fractures can be treated conservatively. We describe a case illustrating a typical presentation of insidious hip pain culminating in sudden onset of severe hip pain in a healthy young man. We perform a literature review of studies showing epidemiology, treatment algorithms and rehabilitation.